Healthcare sciences students perceptions of integrating dgital healthcare into the higher education curriculum - Govender, S.; Kyarkanaye, T.; Naidoo, U. (South African Journal of Higher Education, 2025)
To ensure healthcare professionals excel in a digitally advanced healthcare landscape, they must receive proper training. This study aimed to evaluate the awareness and perspectives of Healthcare Sciences students from various disciplines at a South African higher education institution regarding the integration of digital healthcare into the curriculum. A descriptive quantitative research design was employed, with data collected via an online questionnaire addressing awareness, perceived benefits, and challenges related to digital healthcare curriculum inclusion. Out of 138 participants, 52.9 per cent (n=73) reported a poor understanding of digital healthcare, and 79.7 per cent (n=110) indicated they had not taken a digital health course during their training. A statistically significant correlation (p=0.00) was found between awareness and formal training, suggesting that poor awareness is linked to a lack of formal training. Participants identified the potential benefit of using digital healthcare platforms to open a practice after graduation. However, 55 per cent (n=76) expressed concern that digital healthcare training might negatively affect cultural competence as a clinical skill. Health Sciences training institutions should integrate digital health skills into the core curriculum, emphasizing an experience-based approach. The curriculum should include patient interaction, cultural dynamics, standards and ethics, and technical skill development.